EVALUASI LAPORAN AKUNTABILITAS KINERJA INSTANSI PEMERINTAH PADA SATUAN KERJA NON VERTIKAL TERTENTU PENYEDIAAN PERUMAHAN PROVINSI SULAWESI UTARA - Wantah, Kezia Princesa; Kalangi, Lintje; Tangkuman, Steven (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
LAKIP is the government’s accountability for activities carried out within one budget year and as one of the realization of good governance. The community questioned whether the budget used was appropriate or not with what they received.In addition, accountability reports on public sector organizations are only oriented to "output" rather than "outcome". This resulted public sector organizations to pay more attention to value for money that is able to consider inputs, outputs, especially outcomes that underlie the three main elements namely economy, efficiency and effectiveness.This study aims to find out how the SNVT Provision program in North Sulawesi Province is measured using the concept of value for money.The research method used is descriptive qualitative with the results of interviews and data collected, analyzed and conclusions drawn.The results showed that the evaluation of the SNVT program for the Provision of Housing in the Province of North Sulawesi was measured by the concept of value for money for economic measurements achieving good results. However, the measurement for efficiency and effectiveness are not yet optimum as the budget is not fully realized.